2013
DOI: 10.1109/tmag.2013.2250925
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl-Iron/Epoxy Composite Magnetic Core for Planar Power Inductor Used in Package-Level Power Grid

Abstract: Our research objective is to realize the basic technology for a next generation Package-Level Power Grid (PLPG) for plural application LSIs. In this study, a carbonyl-iron powder (CIP)/epoxy composite magnetic core, for large-current power inductor used for the main dc-dc converter in the PLPG, has been fabricated and evaluated. 54 vol.%-CIP/epoxy composite core made by screenprinting had a relative permeability of 7.5 and loss tangent of about 0.03 at 100 MHz. The planar power inductor using composite core wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…As already reported [4], we forecast that the next generation power delivery to LSIs will become a package-level dc power grid (PLPG). The PLPG will consist of a main buck dc-dc converter with large current inductor and several POL buck dc-dc converters for each application LSI.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…As already reported [4], we forecast that the next generation power delivery to LSIs will become a package-level dc power grid (PLPG). The PLPG will consist of a main buck dc-dc converter with large current inductor and several POL buck dc-dc converters for each application LSI.…”
Section: Introductionmentioning
confidence: 85%
“…BASF Co. showed that the non-reduction CIP has an onion skin structure [9], which may be due to the spherical iron layers form on a nucleus in the Fe-particle growth, and CIP has a narrow particle-size distribution with a mean diameter of 1.1 m. Fig.2 shows the static magnetization curve of the CIP [4]. The CIP had a saturation magnetization of about 2 T and small coercive force.…”
Section: A Zn-fe Ferrite Thick Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the package-level DC power grid has been proposed 1) as the next generation power delivery to LSIs, which consists of a main buck DC-DC converter and the multiple POL converters integrated into the package. Since the power supply voltage for CMOS logic LSI has been lowered to 1 V or below, it is considered that the POL converter operates under low-voltage output condition.…”
Section: …………………………………………(2)mentioning
confidence: 99%
“…Reduction of the iron loss can be achieved using core materials with improved properties and by changing the core shape (10)- (14) . Copper loss is reduced by changing the wire's shape and winding form.…”
Section: Introductionmentioning
confidence: 99%